A trajetória sócio-produtiva da agricultura familiar no município de Novo Barreiro (RS) - Sganzerla, Celso (2019)
Family farming in Novo Barreiro, a municipality in the northwest of Rio Grande do Sul state, has in its socio-productive trajectory the historical accumulation of its experiences, as well as resistance and resilience to the dominant model of agriculture. To investigate this trajectory, we proceeded to a methodological approach that sought: on the one hand to understand, especially in the Brazilian case, the conformation of this social category in recent academic, social and political debates; and, on the other hand, to conduct a field research - through dialogues, interviews and on-site observation of the daily life of the families involved - that sought to evaluate their trajectories, think about their limits and future challenges. In this sense, interviews were conducted with family farmers from various productive segments, interviews with informants considered strategic (public agents and former residents), and also the application of questionnaires to families. Thus, the research can verify that, since the beginning of the occupation of the territory, the different populations that settled there tried to develop ways of production that would guarantee the survival of the family and the maintenance to some degree of customs, quality of life and leisure spaces and community life. Among the results of this work are the identification and characterization of three main groups of family farmers, characterized in this work as: grain and cereal producers, diversified and differentiated and subsistence producers. From there it was possible to reflect, according to the specificity of each of the three modes of production, about the problems that are present in each type of productive combination, about the understanding of their concerns regarding the future of the activity and about the limits. and challenges for the future of these barreirense family farmers.